Timing and intensity of physical activity and late sleeping habits among children in Japan - Matsuyama, Yusuke; Isumi, Aya; Doi, Satomi; Shibata, Ai; Ishii, Kaori; Oka, Koichiro; Fujiwara, Takeo (Frontiers in Pediatrics, 2022)
Background Little is known about what timing and intensity of physical activity (PA) are beneficial to preventing children’s late sleeping habits. We investigated the association between timing and intensity of PA and late sleeping habits among Japanese children. Methods The amount of PA on a weekday (light (>1.5 to <3.0 metabolic equivalents [METs]); moderate (3.0 to <6.0 METs); and vigorous (6.0 to <20.0 METs) was measured for the whole day, before school, during school, and after school, using accelerometers for population-based fourth-grade elementary school and eighth graders for 7 consecutive days between September and December 2018. Late sleeping habit (going to bed after 10 p.m. for fourth graders and after 11 p.m. for eighth graders) was assessed by questionnaires. The data of 229 fourth graders and 182 eighth graders were analyzed with Poisson regression adjusted for grade, gender, household income, body mass index (BMI), belonging to a sports club, wake-up time on weekdays, and PAs with different intensities. Results Total PA was not associated with late sleeping habits. Light-intensity PA before school was protectively associated with late sleeping habits (prevalence ratio [PR]: 0.82, 95% confidence interval [CI]: 0.68, 0.99) while PA at school or after school was not. Conclusion Light-intensity PA before school may enhance the earlier bedtime of children.